Lord Lyons : a diplomat in an age of nationalism and war - Jenkins, Brian, 1939- (McGill-Queen's University Press, 2014)
The British ambassador in Washington during the US Civil War and ambassador in Paris before and after the Franco-Prussian war, Lord Lyons (1817-1887) was one of the most important diplomats of the Victorian period. Although frequently featured in histories of the United States and Europe in the second half of the nineteenth century, and in discussions and analyses of British foreign policy, he has remained an ill-defined figure. In Lord Lyons: A Diplomat in an Age of Nationalism and War, Brian Jenkins explains the man and examines his career. Based on a staggering study of primary sources, he presents a convincing portrait of a subject who rarely revealed himself personally. Though he avoided publicity, Lyons came to be regarded as his nation's premier diplomat as his career took him to the heart of the great international issues and crises of his generation. As minister to the United States he played a vital role in preserving Anglo-American peace and was a powerful voice opposing Anglo-French intervention in the Civil War. While ambassador to the Ottoman Empire, he helped to prevent French control of the Suez Canal then under construction. In France, he maintained an amiable and constructive relationship with a bitter nation struggling to reorganize itself and its constitution after the Franco-Prussian War. For many historians Lord Lyons has been difficult to ignore but hard to admire. In rescuing him as a truly important historical figure, Jenkins details for the first time the personal and public strategies Lyons employed through decades of exemplary diplomatic service on both sides of the Atlantic --